A successful surgical management of pediatric ossifying fibroma in peripheral limited setting: a rare case report - N. O. V., Nur Setyo; Adi Pratama, Yonanda; Praba, I. Komang; Herdini, Camelia; Indrasari, Sagung Rai; Yudistira, Danu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Ossifying fibroma (OF) is a rare non-malignant fibro-osseous lesion of the craniofacial area with the characteristic of slow-growing and locally aggressive. The incidence rate in paediatric patients is still not clear. The management is varied from observation and serial radiologic imaging to radical resection of the tumour. To provide knowledge and information about diagnosing and managing a rare case of craniofacial ossifying fibroma. A-5-year-old boy diagnosed with orbito-inferonasal region ossifying fibroma underwent extirpation of the mass with the lateral rhinotomy- Webber Ferguson approach, anterior orbitotomy by the ophthalmologist, and obturator placement by the prosthodontist. OF remains a rare disease, particularly in paediatric patients, which is locally aggressive although it’s benign characteristic. Definitive excision is the treatment of choice for OF. Successful surgical outcome was due to a multidisciplinary team and surgical incision technique. We found that lateral rhinotomy Weber Ferguson incision showed excellent exposure. Vision and facial nerve function were preserved as well as good facial symmetry and aesthetics and recurrence prevention. Regular follow-up is necessary for young OF patients.